2007
DOI: 10.1038/sj.bmt.1705553
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of cyclophosphamide and busulfan by fludarabine, treosulfan and melphalan in a preparative regimen for children and adolescents with Shwachman–Diamond syndrome

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is the only definitive treatment for severe bone marrow dysfunction and clonal disorders in patients diagnosed with Shwachman-Diamond syndrome (SDS).In an attempt to minimize regimen-related toxicity (RRT), we have initiated a fludarabine/treosulfan/ melphalan-based pilot protocol avoiding the combination of busulfan and cyclophosphamide. Median age at transplantation was 9.6 years (range 1.5-17 years). All three patients received conditioning with flud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Therefore, TREO was explored increasingly in paediatric patients. [3][4][5][6][7] In general, the favourable properties of TREO, and especially the decreased acute toxicity have been confirmed in these paediatric reports. As we also observed an increasing use of TREO in paediatric patients in Germany and Austria during the last 4 years, we decided to perform a formal retrospective analysis of all patients transplanted between 2003 and 2009 and compare it wih a historical control cohort provided by the Paediatric Registry for Stem Cell Transplantation (PRST), which documents all paediatic transplantations in Austria, Switzerland and Germany.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, TREO was explored increasingly in paediatric patients. [3][4][5][6][7] In general, the favourable properties of TREO, and especially the decreased acute toxicity have been confirmed in these paediatric reports. As we also observed an increasing use of TREO in paediatric patients in Germany and Austria during the last 4 years, we decided to perform a formal retrospective analysis of all patients transplanted between 2003 and 2009 and compare it wih a historical control cohort provided by the Paediatric Registry for Stem Cell Transplantation (PRST), which documents all paediatic transplantations in Austria, Switzerland and Germany.…”
Section: Introductionsupporting
confidence: 62%
“…Patients 21 and 36 with Shwachman-Diamond syndrome were previously described by Sauer et al 3 Patients 18 to 32 were included in the retrospective European Group for Bone Marrow Transplantation (EBMT) analysis of paediatric leukaemia patients conditioned with TREO. 7 The two patients with IL-10 receptor deficiency were reported by Kotlarz and Beier et al…”
Section: Previously Published Patientsmentioning
confidence: 99%
“…The significant regimen-related toxicity observed during HSCT in past reports of HSCT for SDS has led to recent interest in reduced-intensity preparative regimens that might ameliorate cardiac and pulmonary toxicities. Sauer et al 36 reported three patients with SDS and BM failure transplanted using a regimen consisting of fludarabine, treosulfan and melphalan. All three patients engrafted rapidly with 100% donor chimerism.…”
Section: Discussionmentioning
confidence: 99%
“…However, complications from HSCT are more common in SDS patients than in patients with idiopathic blood dyscrasias [52]. However, some authors have proposed to use attenuated conditioning regimen has been proposed to limit toxicity [53].…”
Section: Shwachman-diamond Syndrome (Sds)mentioning
confidence: 99%